Difference Of Weight And Low-Density Lipoprotein (LDL) Level Of Rattus Norvegicus On Mediterranean Diet And Unsaturated Ketogenic Diet - Tanuy, Ricky S; Dewi, Dewa AL; Dinata, Mulya (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: Sedentary lifestyle continues to develop, which causes problems such asobesity and coronary heart disease. This is caused by an increase in body weight and LDLlevels that can be overcame with a Mediterranean diet or an unsaturated ketogenic diet.Purpose: To analyze the difference in weight and LDL of Rattus norvegicus on theunsaturated ketogenic diet and the Mediterranean dietMethod: this study was an experimental study on 30 Rattus norvegicus divided into threegroups (control, unsaturated ketogenic, and Mediterranean), each group is divided into two,according to the time of administration (two weeks and four weeks). After the interventionwas completed, bodyweight was calculated, and LDL levels were checked. Then, the data wasanalyzed with one-way ANOVA test. Results: The test results show p < 0.001 in the comparison between the three groups and p <0.05 for comparison in the unsaturated ketogenic group. The Mediterranean diet shows p>0.05, and the control diet leads p> 0.05. The data show that rapid weight loss (2 weeks) andreduction in LDL (in 4 weeks) in the unsaturated ketogenic diet is better than theMediterranean diet or control. For medium-term weight loss (4 weeks), the Mediterraneandiet is better than the neither saturated ketogenic diet nor control.Conclusion: There is a difference in weight and low-density lipoprotein (LDL) level ofRattus norvegicus on the Mediterranean diet and unsaturated ketogenic diet. This favorablecondition might minimize the probability risk of obesity and coronary heart disease.